PERSEPSI PASIEN TERHADAP PERILAKU CARING PERAWAT DALAM MELAKUKAN ASUHAN KEPERAWATAN DI RSUM JOMBANG - Ana Farida Ulfa; Nurul Nurul Khoirun Nisa (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2018)
Nursing is one of professional service that has a paradigm or nursing model that includes four components: human, health, environment and nurse itself. Caring is not just an emotional feeling or simple behavior, nurse performance especially in caring behavior becomes very important in influencing service quality and patient satisfaction especially in hospital. The purpose of this study is to describe the patient's perception about caring behavior of nurses in nursing service at Rumah Sakit Unipdu Medika (RSUM). This research use qualitative research design, with phenomological approach. Data obtained by indeep interview to 10 participants who are undergoing hospitalization in RSUM Jombang. The results of the study illustrate that all participants were not able to provide answers related to patient perceptions of caring nurses behavior, this is because the client has never heard the term caring. In general, however, the patient's expectation of the nurse's attitude in providing nursing care is that the nurse must be able to care for the patient as a parent caring for their child, caring for her sincerely, capable of doing the right, competent, disciplined, empathetic, counseling and health education, competent, frequent visits to patients. Nurses should always improve the knowledge and skills in nursing care, so as to provide comprehensive care and plenary as a form of caring behavior nurse.